Somatostatin-Expressing Interneurons Form Axonal Projections to the Contralateral Hippocampus - Eyre, Mark D.; Bartos, Marlene (Frontiers in Neural Circuits, 2019)
Conscious memories are critically dependent upon the bilateral hippocampal formation, and interhemispheric commissural projections made by mossy cells and CA3 pyramidal cells. GABAergic interneurons also make long-range axonal projections, but little is known regarding their commissural, inter-hippocampal connections. We used retrograde and adeno-associated viral tracing, immunofluorescent and electron microscopy, and in vitro optogenetics to assess contralateral projections of neurochemically defined interneuron classes. We found that contralateral-projecting interneurons were 24-fold less common compared to hilar mossy cells, and mostly consisted of somatostatin- and parvalbumin-expressing types. Somatostatin-expressing cells made denser contralateral axonal projections than parvalbumin-expressing cells, although this was typically 10-fold less than the ipsilateral projection density. Somatostatin-expressing cells displayed a topographic-like innervation according to the location of their somata, whereas parvalbumin-expressing cells mostly innervated CA1. In the dentate gyrus molecular layer, commissural interneuron post-synaptic targets were predominantly putative granule cell apical dendrites. In the hilus, varicosities in close vicinity to various interneuron subtypes, as well as mossy cells, were observed, but most contralateral axon varicosities had no adjacent immunolabelled structure. Due to the relative sparsity of the connection and the likely distal dendritic location of their synapses, commissural projections made by interneurons were found to be weak. We postulate that these projections may become functionally active upon intense network activity during tasks requiring increased memory processing.